TEACHING AND LEARNING TO READ AND WRITETHE QUR'AN USING AL-BARQY METHOD - Fitriana Fitriana; Dwi Mirani; Puspa Dianti (Pascasarjana Universitas Islam Negeri Raden Fatah Palembang, 2020)
This article aimed to reveal the teaching-learning process of how to read and write the Qur'an with the Al-Barqy method to Faculty of Teacher Training and Education students at Sriwjaya University. The research method used qualitative method. The data collection was takenfrom observation, interviews, and documentation. The respondents consisted of students and lecturers of Islamic Education. This research focusedon the learning process of how to read and write the Al-Qur'an using the Al-Barqy method? What are the advantages and disadvantages used in the Al-Barqy method? The information obtained was analyzed with interactive analysis through several components, namely data collection, data reduction, data presentation, and drawing conclusions. Then the data from the observation and documentation were adjusted. This teaching-learning process only emphasized on the ability to read and write the Qur'an in Faculty of Teacher Training and Education students at Sriwijaya University. The result of this research of the teaching-learning process to read and write Al-Qur'an with the al-barqy method made students learn the Qur'an quicker and easiercompared to other methods. This method used easier steps and a fun process. And there were several advantages, namely: Used a short period of time which was up to 8 hours and for adults was only up to 200 minutes to read the Qur’an,can be used for all ages both children and adults. While the drawbacks of this method include: This method was called the 8-hour method meaning that the learning time was relatively short and if it was for children's education then we must pay attention to their conditions both endurance and their memories, the understandings of hijaiyah letters was not very deep.